Surgical Removal of Eye Worm (Ocular Setariasis) in Equines - Ratnu, Devangini A; Parikh, Pinesh V; Kelawala, Divyesh N; Patel, Malhar D; Mahla, Jalendra K (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Ocular setariasis is a common vision threatening ophthalmic condition in equine resulting from ectopic parasitism by Setaria digitata, Setaria equina and Thelazia lacrymalis. The disease occurs mostly in summer and autumn seasons and it displays signs of lacrimation, photophobia, corneal opacity, conjunctivitis and loss of vision. Close inspection of the eye reveals a moving worm in the anterior chamber of the eye. B-mode ultrasonography using linear probe (10-18 MHz) helps in the diagnosis in case of complete opacity. Six horses were represented for ocular setarial worms. The best treatment is the surgical removal of the parasite under regional/ general anaesthesia. Paracentesis of anterior chamber for removal of intraocular parasite through a modified clear corneal stab incision at the limbal margins using 2.8 mm pointed tip 45o angled keratome was found effective. The visual outcome in all eyes was good with restoration of normal vision. The present review/ communication is aimed at report etiology, diagnosis and management of ocular setariasis in equine species